Dynamics of Ring-Cleavage Reactions in Temozolomide Induced by Low-Energy Electron Attachment - Arthur-Baidoo, Eugene; Izadi, Farhad; Guerra, Carlos; Garcia, Gustavo; Ončák, Milan; Denifl, Stephan (Frontiers in Physics, 2022)
We have used a crossed electron molecular beam setup to investigate the behavior of the anticancer drug temozolomide (TMZ) upon the attachment of low-energy electrons (0–14 eV) in the gas phase. Upon a single electron attachment, eight anionic fragments are observed, the most intense being an anion with mass of 109 u at a resonance energy of 0 eV. Quantum chemical calculations suggest that this ion is formed after the tetrazine ring opens along a N–N bond and its fragments leave the molecule, forming an imidazole-carboxamide species. This ion represents the most abundant fragment, with further fragments following from its dissociation. The tetrazine ring cleavage reaction forming N2 is thus the driving force of TMZ reactivity upon electron attachment.